2019
DOI: 10.1186/s12885-019-6218-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nutritional status (CONUT) score as a preoperative risk assessment index for older patients with colorectal cancer

Abstract: BackgroundAssessment of preoperative general condition to predict postoperative outcomes is important, particularly in older patients who typically suffer from various comorbidities and exhibit impaired functional status. In addition to various indices such as Charlson Comorbidity Index (CCI), National Institute on Aging and National Cancer Institute Comorbidity Index (NIA/NCI), Adult Comorbidity Evaluation-27 (ACE-27), and American Society of Anesthesiologists Physical Status classification (ASA-PS), controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 29 publications
3
69
1
Order By: Relevance
“…In the present study, we focused on stage IV CRC including curative resected stage IV CRC and unresectable metastatic CRC, and demonstrated that CONUT score, PNI, and mGPS are independent prognostic factors for OS in patients with stage IV CRC regardless of curative potential. Our results are compatible with previous reports that PNI, mGPS, and CONUT score were prognostic factors in CRC patients undergoing curative resection [5,7,8,14,17], and that CONUT score was a prognostic factor in metastatic CRC patients undergoing chemotherapy [16]. To our knowledge, this is the largest study to date that comprehensively assessed the prognostic signi cance of nutritional and in ammatory measures in patients with stage IV CRC.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we focused on stage IV CRC including curative resected stage IV CRC and unresectable metastatic CRC, and demonstrated that CONUT score, PNI, and mGPS are independent prognostic factors for OS in patients with stage IV CRC regardless of curative potential. Our results are compatible with previous reports that PNI, mGPS, and CONUT score were prognostic factors in CRC patients undergoing curative resection [5,7,8,14,17], and that CONUT score was a prognostic factor in metastatic CRC patients undergoing chemotherapy [16]. To our knowledge, this is the largest study to date that comprehensively assessed the prognostic signi cance of nutritional and in ammatory measures in patients with stage IV CRC.…”
Section: Discussionsupporting
confidence: 91%
“…The CONUT scores, used to assess immuno-nutritional status, were calculated from the following three parameters, as previously described [15,26]: (1) albumin levels of 3.5, 3.0-3.49, 2.5-2.99, and <2.5 g/dL were scored as 0, 2, 4, and 6 points, respectively; (2) total lymphocyte counts of ≥1600, 1200-1599, 800-1199, and <800/µL were scored as 0, 1, 2, and 3 points, respectively; (3) total cholesterol levels of ≥180, 140-179, 100-139, and <100 mg/dL were scored as 0, 1, 2, and 3 points, respectively. Separately, the Child-Pugh classification [27] and ALBI grade [28] were used to assess hepatic functional reserve.…”
Section: Assessment Of Immuno-nutritional Status and Hepatic Functionmentioning
confidence: 99%
“…The Controlling Nutritional Status(CONUT) score, which is calculated from serum level of albumin, lymphocyte and cholesterol, actually re ects state of systemic in ammation, nutrition and immune responsiveness [14]. The prognostic value of CONUT has been con rmed in various clinical settings including cardiovascular disease, liver disease and cancer [15][16][17][18][19]. We designed this study to explore the correlation between CONUT and mortality of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%